Bioenergetics of Human Peripheral Blood Mononuclear Cell Metabolism in Quiescent, Activated, and Glucocorticoid-Treated States. Issue 4 (August 2000) - Schmid, Dirk; Burmester, Gerd-Rüdiger; Tripmacher, Robert; Kuhnke, Antje; Buttgereit, Frank
Abstract : The first quantitative findings on the energy metabolism of human immunecells are presented. In quiescent peripheral blood mononuclear cells(PBMC) protein biosynthesis and Na +, K + -ATPase activity eachaccounted for 8% of cellular oxygen consumption. Stimulation with 25, 50, and 75 μg Con A/ml (1.25, 2.5 or 3.75 μg/10 6 cells) increased totaloxygen consumption within seconds by 8, 36, and 53%, respectively. Afteraddition of 75 μg Con A/ml, the proportion of cellular oxygenconsumption due to protein biosynthesis, Na +, K + -ATPase activity, and Ca 2+ -ATPase activity was 15% each and that due to DNA/RNAsynthesis was 8%. On the basis of these findings the immediate effectsof five different glucocorticoids on cellular energy metabolism wereinvestigated. The various glucocorticoids exerted basically the sameinhibitory effects on Con A-stimulated cellular respiration and individualATP-consuming processes, but differed significantly in potency. Similar toprevious studies on rat thymocytes, the relative potencies of theglucocorticoids were found to be: prednylidene (1.7)<dexamethasone(1.5)<methylprednisolone (1.0)<prednisolone (0.3)0.2). Given their rapidity of onset, these effects must benongenomically mediated. The differences between the relative potencies ofthe various glucocorticoids for these effects and those for the classicalgenomic effects have important clinical implications, in particular forhigh-dose systemic and local glucocorticoid therapy.